Estimating the wage effects of job mobility in Britain - David Campbell (University of Kent, Department of Economics, 2001)
Switching from one job to another would appear to be an important part of an individual's experience within the labour market. In Britain, approximately one in three workers are observed changing jobs over a three year period. Models of voluntary job mobility predict that in the long run, switching jobs exerts a positive effect on lifetime earnings. This long run gain, however, may be generated through either shifts in the earnings profile, or changes in its slope. Using data from the British Household Panel Survey, it is found that the total wage gain arising from mobility over a three year period is around 10%. Further analysis suggests that four-tenths of this gain is generated by an upward shift in the earnings profile at the point of job change and the remaining six-tenths due to the movement into a job with a higher rate of on-the-job wage growth.
Keywords: C23; J31; 330; Job mobility; wage growth; Arbeitsmobilität; Lebenseinkommen; Theorie